Invasive Evaluations for Epilepsy Surgery: A Review of the Literature - ENATSU, Rei (Neurol Med Chir (Tokyo), 2016)
Invasive evaluations play important roles in identifying epileptogenic zones and functional areas in patients with intractable focal epilepsy. This article reviews the usefulness, methods, and limitations of invasive evaluations for epilepsy surgery. Invasive evaluations include various types of intracranial electrodes such as stereotactically implanted intracranial depth electrodes (stereo-EEG), chronic subdural electrodes, and intraoperative electrocorticography. Scalp EEG is distorted by the skull, meninges, and skin. On the other hand, intracranial electrodes provide spatial information with higher resolution than scalp electrodes, thereby enabling further delineation of epileptogenic zones and mapping of functional areas with electrical stimulation. In addition, intracranial electrodes record a wide frequency range of electrical activity, which is not possible with scalp electrodes. The very slow potentials in ictal recordings, known as ictal direct current (DC) shifts and ictal/interictal high frequency oscillations, such as ripples (100–200 Hz) and fast ripples (200–500 Hz), have been correlated with the ictal onset zone and are a sensitive and specific marker for epileptogenicity. Furthermore, several studies reported that the electrical stimulation of epileptogenic zones elicited enhanced cortical evoked potentials, abnormal delayed or repetitive responses, and fast ripples. These responses may assist in the delineation of the epileptogenic cortex as a potential new marker. There are definite risks of complications associated with the use of intracranial electrodes. However, when an invasive evaluation is selected based on careful consideration of the risks and benefits, it provides useful information for establishing a strategy for epilepsy surgery.